Kinerja Manajemen Rantai Pasok Kelapa di Provinsi Sulawesi Tengah - Nur Rahmi Suud; Ria Indriani; Yuliana Bakari (Jurnal Sosial Ekonomi Pertanian, 2021)
This study aims to analyze the condition and performance of the coconut supply chain management at CV. Cakrawala is located in Bunta District, Banggai Regency, Central Sulawesi Province in March - April 2020. The research method is a survey with the type of data is primary data and secondary data. The data analysis used the analysis of the Food Supply Chain Network (FSCN) and the Analysis of the Supply Chain Operation Reference (SCOR). The results showed the supply chain conditions in CV. Cakrawala based on supply chain objectives, supply chain structure, supply chain management, supply chain resources and supply chain business processes are running very well. The flow pattern of the coconut supply chain, especially white copra, on CV Cakrawala, namely Farmers - CV. Cakrawala - PT. Elvatara Indojaya in Surabaya. Meanwhile, the performance of the coconut supply chain based on reliability, responsibility, flexibility, cost and asset management, all are in a superior position.